Improving Operational Efficiency Through Digital Transformation: Implementation of Web-Based Inventory Information System at PT Bintang Delapan Terminal - Muhammad Faisal; Abdul Malik; M. Hasanuddin; Muh. Hajar Harike; Jayanti Yusmah Sa (Journal of Embedded Systems, Security and Intelligent Systems, 2024)
The rapid development of information technology has brought significant changes in the logistics and warehousing sector. PT Bintang Eight Terminal faces challenges in managing inventory manually, causing recording errors and distribution delays. This research aims to develop and implement a web-based inventory control information system to improve the efficiency and accuracy of inventory management. The method used is the Waterfall model, which includes requirements analysis, system design, implementation, testing, and maintenance. The results showed that the new system reduced response time from 10 minutes to 5 minutes, increased data accuracy from 85% to 95%, and increased operational efficiency from 70% to 90%. User acceptance Testing (UAT) showed high satisfaction, noting significant improvements in ease of use and data access speed. In conclusion, this web-based information system is effective in improving operational performance and user satisfaction at PT Bintang Eight Terminal, and demonstrates that automation can have a positive impact in logistics and warehousing operations.